THE PRACTICAL SITUATION OF DEVELOPING INFORMATION SECURITY COMPETENCE IN FUTURE JOURNALISTS (Scientific journal of the Fergana State University, 2023)
This article elaborates and analyzes the practical situation of information security competence development in future journalists.The more complete, accurate, and objective journalistic information is, the higher the model of the external world for each person using this information will be consistent with this world